2020
DOI: 10.37237/110202
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Language Learning in a Work-cycle: Learners’ Perceptions, Beliefs and Behaviors

Abstract: The present study reports on an attempt to apply the principles of autonomous learning within the curriculum of an online course for teaching English to Iranian adult language learners. The contents of the course (i.e. general English) were delivered using work-cycles (Legenhausen, 2003) and were completed in the form of students’ projects. Each work-cycle started by setting personal learning goals in the planning and negotiation phase, deciding on the project in the decision-making phase, completing the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…They could also evaluate their own learning from the instant feedback for each exercise. This is in line with Sadaghian, et. al.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…They could also evaluate their own learning from the instant feedback for each exercise. This is in line with Sadaghian, et. al.…”
Section: Resultssupporting
confidence: 93%
“…As for teachers' role they act more as a facilitator. This is in line with Sadaghian, et. al (2020) who said, "Computer Assisted Language Learning (CALL) environment provide an ideal support for the teacher as facilitator …" (p. 70).…”
Section: Introductionsupporting
confidence: 93%
“…Learning is viewed as an activity that students do for themselves in a proactive way rather than as a covert event that happens to them in reaction to teaching", at the same time, among the key skills of a student who is able to regulate their learning process independently ("self-regulated learner") the author calls the ability to set goals, manage their time, apply different learning strategies, motivate themselves to achieve the goal [13]. In the European tradition, they talk about autonomous learning and the concept of educational autonomy [9,11], the analysis of which shows similarities with the given examples. Ultimately, the researchers argue that targeted training in the implementation of special actions will contribute to the readiness of students for effective distance learning, in which the role of the teacher will be reduced to determining the overall strategies of the educational route, and the student learns to make decisions on its development independently.…”
Section: Theory Of Independent Learning Activitiesmentioning
confidence: 99%
“…Numerous researchers and scholars have shown that learner autonomy contributes to success in EFL learning (Hsieh & Hsieh, 2019;Koirala, 2020;Orawiwatnakul & Wichadee, 2017;Tayjasanant & Suraratdecha, 2016;Tran, 2020). Little (1997; as cited in Sadaghian et al, 2020) stated that autonomous learners are motivated and reflective learners, leading to efficient and effective learning. Furthermore, the level of learning success depends on the degree of autonomy.…”
Section: Introductionmentioning
confidence: 99%